(untitled) (Colombia Medica, 2012)
Brilliant, simple, reserved, supportive friend, enthusiastic colleague, tireless worker, teacher. Adjectives that shelter the memory of someone who left an important legacy for public health, pediatrics and teaching in public health, focused mainly on nutrition. Doctor and Surgeon at the National University of Colombia (1956), Dr. Alberto Pradilla was one of the few Colombian doctors who, in addition to his medical specialty as a pediatrician, was trained in the area of ​​nutrition.